Pengembangan Modul Pembelajaran Kimia Berbasis PBL untuk Sekolah Penggerak Fase F SMA/MA pada Materi Hidrolisis Garam - Naibaho, Sriwahyuni; Suryani, Okta (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
This study aims to determine the level of validity and practicality of the chemistry learning module which was developed as teaching material for Sekolah Penggerak especially for salt hydrolysis material. This learning module is structured using the problem-based learning model, as a solution that is being faced by teachers in the Kurikulum Merdeka to carry out problem-based learning. The research method used is development with the Plomp model developed by Tjeerd. The stages of this development research consisted of initial investigations, prototype design and assessment, with the type of data used namely primary data collected through validation and practicality instruments. Module validation data was obtained from 3 chemistry lecturers at UNP and 2 chemistry teachers at SMAN 15 Padang, while the practicality data for the module came from 2 chemistry teachers at SMAN 15 Padang and 20 Phase F students at SMAN 15 Padang. The results of research on module development obtained an average value of Aikens'v validity of 0.86 with a valid category, while the results of module practicality by teachers obtained an average percentage of 92% with a very practical category and the average result of the practicality percentage by students was 91% in the very practical category. Based on the results found and also the one to one evaluation that was carried out before, it can be concluded that this chemistry module can already be used in the implementation of learning for Sekolah Penggerak. This learning module is expected to be one of the solutions for teachers to carry out learning in accordance with the demands of the Kurikulum Merdeka in Sekolah Penggerak to create students who are creative, independent and think critically.